2022
DOI: 10.21203/rs.3.rs-1662988/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Motives for COVID-19 vaccine hesitancy amongst marginalized groups, including homeless persons and migrants, in France: a mixed-methods study.

Abstract: Background: Persons experiencing unstable housing – including recently arrived migrants – are at elevated risk of contracting COVID-19 and suffer from high morbidity and mortality. In this context, the COVID-19 vaccine was foreseen as a promising way to control the pandemic and reduce social inequalities in this area. Understanding the motives of COVID-19 vaccine acceptability in people with unstable housing, including migrants, is therefore crucial to tailor public health communication and outreach. Thus, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…These data underline the importance of awareness-raising and sensitization by trusted third parties such as homeless organizations, social workers, mediators, and site managers, in line with qualitative studies 29 , 30 . Our data also show the positive impact on vaccine uptake by support mechanisms and follow-up by medical professionals and/or by social organizations.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…These data underline the importance of awareness-raising and sensitization by trusted third parties such as homeless organizations, social workers, mediators, and site managers, in line with qualitative studies 29 , 30 . Our data also show the positive impact on vaccine uptake by support mechanisms and follow-up by medical professionals and/or by social organizations.…”
Section: Discussionsupporting
confidence: 78%
“…Individuals opposed to vaccination comprised a minority in our sample (12% of non-vaccinated), as compared to hesitant people, with 54% afraid of vaccine effects. Comparable findings were found in a mixed-methods study among French PEH (52% reportedly afraid of vaccine 29 ) and in a multicentric survey among undocumented migrants 40 . Association of positive views on vaccination with COVID-19 vaccine uptake was highlighted in several articles 31 , 33 , 34 , 40 , 43 .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Supplementary Table S1 details the included studies, which were descriptive or observational in design. The most common country of origin was the United States [ 29 31 , 35 37 , 39 , 40 , 43 , 46 , 47 , 50 , 59 , 62 , 67 ], then France [ 27 , 32 , 33 , 38 , 41 , 42 , 44 , 45 , 52 , 56 , 60 ], with further contributions from Wales [ 63 , 65 , 66 ] and Denmark [ 34 , 48 , 49 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies explored the trends of COVID-19 vaccine uptake. Two were high quality [ 49 , 60 ] and four were moderate quality [ 33 , 45 , 55 , 67 ]. Overall, the studies found that people experiencing homelessness were less likely to have received both doses of the vaccine than their housed counterparts.…”
Section: Resultsmentioning
confidence: 99%